the Profit Control , the Present and Future Accounts (Al-Mansour Journal, 2022)
Practical experiences have affirmed that the specific quality of the Iraqi economy as embodied by the supremacy of the supremacy of the oil sector have not resulted in positive results and clear structural changes concerning the development of this economy in all its productive and civil- service sectors. The increasing dependence on this source has made the economy suffer from continuous crises and big problems especially when the prices of oil have recently come down.As a fact, the supremacy of oil revenue at this degree could considered as a short coming in the administration of economic system. The necessity of applying active and clear economic policy at this period thus emerges, enhancing the aim of vary the sources of the income, reforming the structure of the economic sectors and changing their basic entity. The research has basically aimed at defining the structural factors through which we can seriously and actively arrive at, applying the policy of varying the strands of the Iraqi economy and of reforming its structure. This would enable us to face the crisis of the obvious reduction of financial sources and oil revenues.In the light of realistic factors, the research has ended with proposing a strategy that defines the works of the future economic policies. On the level of the short – term policies, we have to reform the system of taxation, activate the work of taxes administration, end the state of widespread corruption and finally, minimize the expenses of services through giving full authority to the system of financial supervision in all state institution.On the level of long – term policies, the study has come up with various suggestions among which are activating the productive sectors (agriculture and industry) and raising their standards so as to vary the Iraqi economy and allow it to get rid of the hegemony of the increasing profits phenomenon.